2017
DOI: 10.1080/13854046.2017.1312700
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the sensitivity of the Personality Assessment Inventory symptom validity tests in detecting response bias in a mixed neuropsychological outpatient sample

Abstract: Findings indicated that exaggerated cognitive dysfunction tends to be present when NIM is very high and that evidence exists for a defensive response style on the PAI in the context of PVT failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Since this study, several simulation studies have examined the CDF for detecting malingering of mental illness (e.g., Bagby, Nicholson, Bacchiochi, Ryder, & Bury, 2002;Blanchard, McGrath, Pogge, & Khadivi, 2003;Greene, 2005). A recent study examining knowngroups by Gaasedelen et al (2017) showed the CDF was not able to significantly discriminate between clinical outpatients who passed and failed 2 or more PVTs. Rogers, Bagby, & Dickens, 1992) and individuals who were determined to be honest was examined.…”
Section: Cashel Discriminant Function (Cdf)mentioning
confidence: 98%
See 4 more Smart Citations
“…Since this study, several simulation studies have examined the CDF for detecting malingering of mental illness (e.g., Bagby, Nicholson, Bacchiochi, Ryder, & Bury, 2002;Blanchard, McGrath, Pogge, & Khadivi, 2003;Greene, 2005). A recent study examining knowngroups by Gaasedelen et al (2017) showed the CDF was not able to significantly discriminate between clinical outpatients who passed and failed 2 or more PVTs. Rogers, Bagby, & Dickens, 1992) and individuals who were determined to be honest was examined.…”
Section: Cashel Discriminant Function (Cdf)mentioning
confidence: 98%
“…From a construct standpoint, it seems logical to distinguish between PVT and SVT because reporting symptoms and characteristics on a self-report inventory is simply a different process than engaging in a performance-based cognitive task (Larrabee, 2012). As PVTs and SVTs both fall under the umbrella of response bias, it nonetheless remains plausible that they would be related, and generally research has demonstrated a weak to modest relationship between PVTs and SVTs (e.g., Gaasedelen, Whiteside, & Basso, 2017;Keiski, Shore, Hamilton, & Malec, 2015;Patrick & Horner, 2014;Temple, McBride, Horner, Taylor, 2003).…”
Section: Performance Validity and Symptom Validitymentioning
confidence: 99%
See 3 more Smart Citations